Religious-spiritual correlates of strength of hope and meaning of life among oncology patients - Wnuk, Marcin; Marcinkowski, Jerzy Tadeusz; Hędzelek, Mateusz; Świstak-Sawa, Sylwia (Psychoonkologia, 2010)
The aim of the study was to verify if among oncology patients there is the relationships between religious-spiritual variables and meaning of life as well as strength of hope. Additional aim was to identified other meaning of life and strength of hope positive and negative correlates connected with recovering process and preferable values. Material and methods : The sample consisted of 50 oncology patients recovering in three Warsaw Medical Center. The following tools were used: Santa Clara Strength of Religious Faith (SCSORF), Daily Spiritual Experiences Scale (DSES), one-item scales regarding frequency of prayer and frequency of church attendance, Purpose Inventory of Life (PIL), Herth Hope Index (HHI), other one-item scales regarding preferable values, attending to psychology, length of being treatment, length of being ill, quantity of friends, feeling of being loved and feeling of being lonely. Results : Noticed positive relationship between strength of hope and meaning of life, frequency of spiritual experiences and strength of hope, frequency of spiritual experiences and age, felling of being loved and strength of hope as well as negative correlations between length of being ill and meaning of life and quantity of friends. There were strong positive relationship between every used measures of religiosity. Conclusions : Among oncology patients spiritual experiences play an important role for strength of hope the same as felling of being loved. Duration of illness has an negative impact on meaning of life and quantity of friends. Among oncology patients motivational and behavioral aspect of religiosity are precisely connected. None of preferable patients values was not the source of hope and meaning of life.